The composition and interests of Russia's business lobbies: A test of Olson's "encompassing organization" hypothesis - William Pyle; Laura Solanko (Bank of Finland, Institute for Economies in Transition (BOFIT), 2010)
Why are some lobby groups less benign in their external effects than others? Nearly three decades ago, Mancur Olson (1982) proposed that less-encompassing lobby groups with their constituents collectively representing a narrow range of sectors are more apt to seek the types of subsidies, tariffs, tax loopholes, and competition-limiting regulations that impose costs on the rest of society. To the best of our knowledge, Olson s oft-cited hypothesis has yet to be actually tested, due perhaps to the absence of adequate data on general policy preferences of various types of lobbies. Thus, we examine a pair of surveys from 2003 and 2004 which were targeted at managers of business associations (lobby groups) and their enterprise constituents to directly test Olson s hypothesis. Managers from a diverse array of Russian industrial firms and business associations were asked similar questions regarding their attitudes to policies that explicitly benefit well-defined sectoral or regional interests and, implicitly, impose external costs. The pattern of responses is striking. Managers of less-encompassing associations and the constituent firms of such groups are much more apt to see such policies in a favorable light. In contrast, more-encompassing associations and their member display greater skepticism toward narrowly targeted government interventions. Our results strongly support Olson s hypothesis.
URN:NBN:fi:bof-201408071949
Keywords: 330